Pós-tratamento físico-químico de efluente sanitário proveniente de reator UASB - Moreira, Fernando Guimarães (2024)
The application of the water treatability process with the use of the jar test apparatus is surely extremely useful and it is also the most used method to evaluate the processes of coagulation, flocculation, as well as the subsequent steps of decantation and filtration (known as clarification step). Sewage, in general, has 99.9% of water and only 0.1% of solids and several are the processes used for its treatment. The anaerobic technology, although widely used in Brazil, has a BOD removal limitation between 65 to 75% for UASB reactors. The application of processes called tertiary, that is, post biological treatment, has been widely used, and, among these processes, there is the assisted chemical treatment, which consists mainly in the application of a coagulant agent in the effluent after biological treatment. The present study used the treatability process from the application of the coagulant agent polyaluminum chloride (PAC), varying its concentrations from 70 mg/L to 240 mg/L and pH of 5.5 to 8.0 in effluents after biological treatment in UASB type reactors, collected from the sewage treatment plant of the city of Araguari/MG. The dosage of the coagulant agent (110 mg/L) associated with a 6.70 pH provided the best reductions of the color and turbidity parameters. Comparing the analyzed parameters of the samples after the treatability process with the values found after filtration, the average reductions were 64.38% for turbidity, 44.63% for apparent color and the average reductions of BOD, COD, and Phosphorus, reached 35,43%, 27.16 and 66.38%, respectively. Besides, the average reduction was 76.56% for the TSS’s. When comparing the values of the effluent parameters collected at the output of the UASB reactors, with the filtered effluent after the coagulation/flocculation, decanting and filtration processes, the average values of reductions were: (1) for turbidity 98.99%; (2) for apparent color 90.54%; (3) for BOD 82.81%; (4) for COD 81.99%; (5) for phosphorus 99.52%, and (6) for TSS 97.47%. Thus, it was experimentally concluded that the chemically assisted treatment followed by deep filtration with double layer filters (sand and anthracite) is a promising process of polishing effluents from anaerobic systems of sewage treatments.